Optimization of Manufacturing Parameters for Below-Knee Prosthetic Sockets Based on 3D Printing Using the Taguchi Method - Pilargenta , Higan; Lestari, Wahyu Dwi (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Fused Deposition Modeling (FDM) technology is widely applied in the fabrication of transtibial prosthetic sockets due to its operational simplicity and high design flexibility. However, prolonged printing time remains a major constraint in improving production efficiency for clinical and industrial applications. This study aims to optimize the printing time of transtibial prosthetic sockets by adjusting three process parameters: socket wall thickness (1, 2, and 3 mm), thermoplastic filament type (PLA, ABS, and PP), and nozzle diameter (0.4 mm, 0.6 mm, and 0.8 mm). The Taguchi method with an L9 orthogonal array was employed as the experimental design. All specimens were fabricated using a Flashforge Guider II Series printer, and the printing time was evaluated using the Signal to Noise (S/N) ratio with the “smaller is better” criterion and analysis of variance (ANOVA) at a significance level of α = 0.05. The results indicate that nozzle diameter has the most significant effect on printing time, contributing 55.40%, followed by wall thickness at 39.51%, while material type contributes only 1.24% and is not statistically significant. The optimal parameter combination 1 mm wall thickness, PLA filament, and a 0.8 mm nozzle diameter reduced the average printing time by 24%, with a coefficient of variation below 5%. Confirmation tests yielded a validation S/N ratio of −64.58 dB, confirming the stability of the printing process. These findings provide practical guidance for accelerating the production rate of FDM based prosthetic sockets and suggest further research focusing on mechanical performance evaluation, infill pattern variation, and multi objective optimization.